Psychometric Evaluation of the Meaning in Life Questionnaire in Islamic Boarding Schools - NOVI HIDAYAT; Muhammad jayyid; Dikut Affan Aryansyah (STABN RADEN WIJAYA WONOGIRI, 2026)
Meaning in life is an important psychological resource that contributes to adolescents’ well-being, academic engagement, and positive development. However, empirical evidence regarding the psychometric properties of the Meaning in Life Questionnaire (MLQ) among students in Islamic boarding schools (pondok pesantren) remains limited. This study aimed to examine the construct validity and reliability of the MLQ in the context of Islamic boarding school education in Indonesia. A quantitative methodological design was employed involving 125 students aged 14–17 years from several Islamic boarding schools in Banjarnegara Regency, Central Java, Indonesia. Data were analyzed using Confirmatory Factor Analysis (CFA) with LISREL 8.80. The findings revealed that only one indicator met the recommended criterion for convergent validity (λ = 0.51; t = 6.13), whereas most indicators demonstrated relatively low factor loadings, and two indicators exhibited negative and non-significant loadings. Despite these limitations, the overall measurement model demonstrated an acceptable level of fit (χ² = 45.22, p = .12, RMSEA = .049, GFI = .93, SRMR = .073). The findings suggest that the original MLQ does not fully capture the culturally embedded meaning of life among santri and requires further cultural adaptation and psychometric refinement